Sorption characteristics of cement composite reinforced with some locally available lignocellulosic materials in Nigeria (2013)
The aim of this study was to investigate the sorption property of wood cement composite produced from bagasse (Saccharum officinarum), bamboo (Bambusa vulgaris) and coir (Cocos nucifera L). The mass of the fibre varies from 1 to 6% of the mass of cement. The result indicated that the mass fraction has significant effect on the sorption properties of the composites. Water absorption (W.A.) rate increases with increase in the fibre content of the composites. Thickness swelling (T.S.) in all the composites was less than 1.7% at 24 h water immersion at room temperature. There was linear correlation between mass fraction, water absorption and thickness swelling of the composites. The relatively low W.A. capacity and T.S. at content less than 3% of mass of cement suggests that they can be employed in outdoor situations and at this level they are dimensionally stable but beyond this level it is not advisable.